Health-Promoting Lifestyle among People Without Heart Disease in Isfahan - Dehkordi, Leila Mardanian (Int J Prev Med, 2018)
BACKGROUND: The present research conducted with aim to determine the health-promoting behaviors (HPBs) of public of Isfahan, and study the associations of HPBs with demographic characteristics. METHODS: In a cross-sectional study conducted on 369 people without heart disease living in Isfahan, HPBs were assessed using a questionnaire which consists of two parts: personal information and Health-Promoting Lifestyle Profile II (HPLP-II). Data were analyzed by t-test and one-way analysis of variance. RESULTS: The mean score for overall HPLP-II (158.30 ± 19.38) indicated the acceptable level of performing HPBs in Isfahan. Physical activity got the lowest score (16.36 ± 5.13), and the highest score was for interpersonal relations (53.16 ± 5.59). There were significant differences on physical activity and interpersonal relation dimensions between males and females (P < 0.05). The mean score of physical activity was highest in single participants (P < 0.05). Mean score of physical activity for people with college education was greater than others (P < 0.05). Overall HPLP-II and its domains mean scores for people that received education about prevention of cardiovascular disease were greater than others (P < 0.05). CONCLUSIONS: Results showed HPBs in people of Isfahan society is acceptable but physical activity is in the worst condition. The role of physical activity in preventing and controlling cardiovascular disease is well established. Therefore, it seems that providing information about physical activity can lead to an improvement of health-promoting lifestyle.